SUPERVISI PENDIDIKAN DALAM PERSPEKTIF EPISTEMOLOGI ISLAM - Moch Wahid Ilham (Nurul Jadid University, 2017)
This paper presents about the supervision of education in the perspective of Islamic epistemology. Changes in an increasingly advanced era makes the school as an educational institution, is required to produce a generation that can answer the needs of the community. To give birth to such qualified generation, of course, can not be separated from the role of educational institutions, and educational personnel who must be qualified. It will be born with the supervision of education, conducted by the duty. The role of the principal as a supervisor is a major role that the principal assumes, as a supporter of the educational process in school. However, the reality that exists, the majority of principals have not understood well related to its role. To provide a deeper understanding of the sources of educational supervision, this paper will explain the supervision of education in the perspective of Epistemology, which is one of the branches of philosophy, and examines the origin of an inquiry, in this case the supervision of education. By understanding the source of educational supervision, it is expected that supervisors are able to perform their role well.